Implementation of Raspberry Pi PICO as PLC for Monitoring and Control in Swiftlet Cultivation Based on Weintek HMI - Satrio Sarwo Mumpuni; Rini Puji Astutik (G-Tech: Jurnal Teknologi Terapan, 2025)
Swiftlet farming is one of the promising cultivation efforts for breeders because it can generate multiple and sustainable profits. Large profits will have an impact on the economy of the community, especially swiftlet breeders. The use of technology to provide ideal conditions for swiftlet farming will greatly affect the quality of the swiftlet nests. The use of technology in providing an ideal environment for swiftlet cages cannot be separated from a system that is designed and reliable in extreme conditions. Raspberry Pi Pico which has an ARM Cortex processor is one solution to the technology used. The implementation of Raspberry Pi Pico into a PLC is one alternative in the development of technology in swiftlet farming. The Raspberry Pi Pico PLC was chosen because it is cheap and has been proven to be reliable in the industrial world. Control of the swiftlet farming room with a room temperature of 25 - 27 ℃ and humidity of 80 - 90%. The LM35 sensor with ladder programming using raspberry pi pico compared to sensors on the market, namely the HTC-1 digital thermometer, has an error of 2.02%, and testing of the soil moisture sensor which has been tested with an error of 1.31%. HMI wientek can display temperature and humidity well and has industrial standard reliability that can be used nonstop 24 hours. The use of raspberry pi pico as a PLC has many advantages and is easy to use because it can use the Mitsubishi PLC program, namely GX Work2.